UNGKAPAN PANTANG LARANG MASYARAKAT MELAYU BELANTIK - Elvina Syahrir (Madah: Jurnal Bahasa dan Sastra, 2016)
The study aims to describe about abstinence forbids of Belantik Malay community and to obtain to know meaning and value that contained in the abstinence forbids. The writer found that there were twenty three abstinence forbids of the Belantik Malay community. By applying qualitative descriptive method, it is obtained that the abstinence forbids observed in Belantik Malay contain in terms of the religion, education, custom, and health. In fact, the abstinence forbids had a magic power that used as a guidance the way of life of Belantik Malay community. They believe that they will get side effects if they disobey them individually and in their group.